Avaliação de protocolos de comunicação no contexto da automação residencial - Pontes, Aline dos Santos (2024)
The concept of the Internet of Things (IoT) refers to the interconnection of technologies aimed at facilitating people’s routines. This control is carried out by wireless communications that follow certain protocols to send and receive information from a central unit. Protocols manage the data between the action and the response of the devices. This dissertation investigates whether Matter, a communication protocol that runs on any IP stack, can provide a consistent experience across different transport layer standards, such as Wi-Fi and 802.15.4. Although Wi-Fi was designed for high data rates and 802.15.4 for IoT, Matter devices may present different experiences depending on the standard used. The most widely used standards for home automation, such as Wi-Fi, 802.15.4 (including ZigBee and Thread), Bluetooth, and LoRa, are well established in the market, and their performance has been extensively studied. This dissertation does not aim to assess the limits of these protocols but rather to verify if Matter offers a consistent experience among them, given that a typical home would likely operate well within the limits of any protocol used. First, the quantity of devices representing a highly automated typical home is established. Then, the typical traffic based on the commonly found devices is determined. Two residential scenarios are simulated: a 100 m2 house and an 800 m2 house, both with devices distributed throughout all rooms, considering a communication frequency of one message every 60 seconds. The performance of the main wireless communication protocols is evaluated under these typical conditions, considering energy consumption, latency, range, and interference. Additionally, more demanding scenarios are analyzed, increasing the node density in an 800 m2 house and the communication frequency to one message every 10 seconds. These conditions aim to test the performance of the protocols under higher demand situations. It is concluded that when protocols are analyzed in the context of Matter, although the protocol provides an abstraction layer that facilitates interoperability and uniform communication between devices of different network technologies, the physical and operational characteristics of Wi-Fi and IEEE 802.15.4-2003 may result in perceptible performance differences to the user. As observed in the simulations, these protocols exhibit entirely different behaviors depending on the scenario in which they are applied.For scenarios with interference from another wireless network in the environment, Wi-Fi delivers almost 40% fewer packets compared to the same scenario without interference. The IEEE 802.15.4-2003 standard maintains delivery integrity and latency across all analyzed scenarios.